Comparative Analysis of Conventional and Sharia Monetary Policies and Instruments in Indonesia - Chandra; Yadi Janwari; Sofyan Al-Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In various literature on economics, the economy is divided into two sectors: the real sector which indudes the service market and the goods market, and the monetary sector which consists of the money market and capital market. In some economic systems, the monetary (financial) flows in a country will affect economic performance. Monetary economics can be applied in a policy called monetary policy. In a conventional discussion, a monetary policy is carried out to achieve an increase in national income, to stabilize market prices and control the rate of inflation. To achieve these macroeconomic objectives, interest rates are used where this is a weakness of conventional monetary stems. The use of interest rates has subsequently caused an economic crisis, even a global financial crisis. In connection with the need for a new economic system, the Islamic monetary system offers a solution to overcome the financial crisis. The system offered is an asset-based transaction, interest-free, avoiding transactions that contain speculation and uncertainty. Next, use stable currencies, namely dinars and dirhams